Religious Belief Model dalam al-Qur’an: Rekonfigurasi Dorongan Perubahan Tindakan Ketaatan - Chandra Kartika Dewi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Religious Belief Model in the Quran: Reconfiguration of Motives for Change Acts of ObedienceThe tendency to change behavior in a more spiritual direction is identified by encouraging education and the implementation of worship routines. The identification ignores the basic structure of the formation of religious action that arises as the main consequence of religious belief. This study aims to show the basic construction of a religious activity contained in the Qur'an as the primary guide for every action of Muslims. To achieve this goal, this study uses qualitative methods with a type of literature study strengthened by content analysis to analyze verse, which is identified by thematic method. This study found that the basic concepts that encourage religious action in Islam come from religious beliefs that are indicated by the emphasis on the form of religious threats and the benefits obtained as the desired expectation to encourage religious behavior. Two types of means arise from within the individual, which is reinforced by external impulses whose emphasis is directed at aspects of religious commitment. The formation of beliefs and the impetus towards commitment are independent variables that allow it to be modified as a way to encourage a more religious change of action. Any effort to change behavior, whether by education or worship, is a form of modification to religious beliefs and commitments.